The Utilization of Digital Media in Islamic Religious Education Learning at MTsN 1 Surakarta: A Qualitative Study of PAI Teachers - Gibraltar, Qais Mu’taz; Hafidz, Hafidz (Journal of Educational Sciences, 2025)
This study investigates the utilization of digital media in Islamic Religious Education (PAI) learning at MTsN 1 Surakarta in response to the growing demand for innovative and relevant pedagogical approaches in the digital era. The research aims to explore the types of digital media used by teachers, their pedagogical intentions, challenges encountered, and their perceptions of digital media effectiveness in embedding Islamic values. Adopting a qualitative approach with a case study method, data were collected through semi-structured interviews and documentation and analyzed using the Miles and Huberman model. The findings show that teachers employ various digital tools such as YouTube videos, Google Classroom, PowerPoint, and Google Forms to enhance student engagement and contextual understanding. Despite challenges like limited access to devices and varying levels of digital literacy, teachers implement adaptive strategies, including simplified media, use of school computer labs, and peer learning communities. The integration of digital media has shifted the teachers’ roles into curators of ethical content and facilitators of digital spiritual learning. This study concludes that digital media, when thoughtfully applied, can reinforce cognitive, affective, and spiritual dimensions of religious education while maintaining Islamic values in a technologically driven learning environment.